P292 10 Hz rTMS induces long-term depression of GABAergic neurotransmission. Issue 3 (March 2017) - Lenz, M.; Galanis, C.; Müller-Dahlhaus, F.; Opitz, A.; Wierenga, C.J.; Szabó, G.; Ziemann, U.; Deller, T.; Funke, K.; Vlachos, A.
Abstract : Question: The cellular and molecular mechanisms of rTMS-induced neural plasticity remain not well understood. Recent experimental evidence obtained in mouse brain slice cultures disclosed that 10 Hz repetitive magnetic stimulation (rMS) induces long-term potentiation (LTP) of excitatory neurotransmission. These studies support the notion that rTMS acts through the induction of 'LTP-like' plasticity. Here, we tested whether rTMS increases cortical excitability by mediating long-term depression (LTD) of inhibitory neurotransmission. Methods: Immunohistochemistry, fluorescence recovery after photobleaching, GABA-uncaging experiments and paired whole-cell patch clamp recordings were used in entorhino-hippocampal slice cultures to study the effects of 10 Hz rMS on structural and functional properties of inhibitory synapses of CA1 pyramidal neurons. Results: We report that 10 Hz rMS reduces dendritic but not somatic GABAergic neurotransmission onto CA1 pyramidal neurons. These functional changes are accompanied by structural remodeling of inhibitory postsynapses and depend on the activation of voltage gated sodium channels, L-type voltage gated calcium channels, NMDA-receptors, and calcineurin protein phosphatases. Consistent with these findings, a reduction in gephyrin cluster sizes and numbers is detected in CA1 stratum radiatum 2 h after 10 Hz rTMS of anaesthetized mice. Conclusion: rMS appears to be a potent tool to induce Ca 2+ -dependent structural and functional changes of both excitatory and inhibitory synapses. We propose that 10 Hz rTMS may shift excitation/inhibition-balance in neuronal networks by inducing LTP of excitatory and LTD of inhibitory neurotransmission. (Supported by DFG and Federal Ministry of Education and Research, Germany; GCBS-WP1.)